PENINGKATAN PERAN SWASTA DALAM PENGEMBANGAN SUMBERDAYA AIR = IMPROVEMENT PRIVATE SECTOR ON WATER RESOURCES DEVELOPMENT - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT As already decided by the government that in The Second Long-term National Development Program was directed to transform the agricultural subsistence to industrial one with strongly supported by agro-industry. Water resources are the main factor in the transformation development. The government has performed the commitment to realize the development that can be identified from the amount of investment allocated to water resources development. However, as the financial sources are getting limited, participation from private sectors is strongly needed. Considering that water has multi function and it is needed by human being, the participation must consider the various demand of water. A conceptual model has been created under the pattern of cooperation between the government and private sector. The pattern of cooperation means the level of development and various demands of water resources have been the focus consideration of model development. Verification of the model was conducted qualitatively at some selected river basins in West Java, Central Java and East Java.